Selective pressure of antibiotics on ARGs and bacterial communities in manure-polluted freshwater-sediment microcosms - Xiong, Wenguang; Sun, Yongxue; Ding, Xueyao; Wang, Mianzhi; Zeng, Zhenling (Frontiers in Microbiology, 2015)
The aim of this study was to investigate selective pressure of antibiotics on antibiotic resistance genes (ARGs) and bacterial communities in manure-polluted aquatic environment. Three treatment groups were set up in freshwater-sediment microcosms: tetracyclines group, sulfonamides group and fluoroquinolones group. Sediment and water samples were collected on day 14 after treatment. Antibiotic concentrations, ARGs abundances and bacterial community composition were analyzed. Antibiotic concentrations were determined by ultra-performance liquid chromatography-electrospray tandem mass spectrometry. ARGs abundances were quantified by real time quantitative PCR. Bacterial community composition was analyzed based on amplicon sequencing. Of the three classes of antibiotics analyzed in the treatment groups, accumulation amounts were tetracyclines> fluoroquinolone> sulfonamides in the sediment samples, while they were sulfonamides> fluoroquinolone> tetracyclines in the water samples. In the treatment groups, the relative abundances of some tet resistance genes (tet(W) and tet(X)) and plasmid-mediated quinolone resistance (PMQR) genes (oqx(B) and aac(6’)-Ib) in sediment samples were significantly higher than those in the paired water samples. Tetracyclines significantly selected the bacterial classes including Gammaproteobacteria, Clostridia, and the genera including Salmonella, Escherichia/Shigella, Clostridium, Stenotrophomonas in sediment samples. The significant selection on bacterial communities posed by sulfonamides and fluoroquinolones was also observed. The results indicated that sediment may supply an ideal setting for maintenance and persistence of tet resistance genes (tet(W) and tet(X)) and PMQR genes (oqx(B) and aac(6’)-Ib) under antibiotic pollution. The results also highlighted that antibiotics significantly selected specific bacterial communities including the taxa associated with opportunistic pathogens.